A graph theory based energy efficient clustering techniques in wireless sensor networks - Kannadhasan, S.; KarthiKeyan, G.; Sethupathi, V. (2013 IEEE Conference on Information and Communication Technologies, 2013)
Energy Efficiency is important role of the Wireless Sensor Networks Researchers. The Energy Efficiency is one of the roles where the data is transmitted to the base station. Energy Techniques is used to improve the reliability of a link. When the data is transmitted communicates to the nodes at exact power to the clustering technique algorithm using graph theory approaches. Secure data aggregation is a challenging task in the wireless sensor networks. These issues are needed to overcome using the clustering efficient techniques. We propose a graph theory based secure data aggregation which has a three phases. We assume the transmitted power and sensing power of the nodes. First phase performs the clustering and cluster head election process. Second phase performs the each clusters are calculated the distance, Energy and also dependence. Third phase performs the shortest path calculation was transmitted the data to secured or not. Finally the aggregated data was transmitted from the cluster heads to the base station. Our proposed models are analysis the acknowledgement through the base stations.